The other sheep, resistant but forgotten: Archetypal characterization of Linca sheep farmers in Argentine Patagonia - Reising, Carlos Aden (2022)
Identifying and understanding how resilience is generated in a local socioecological system is essential for the design of future conservation strategies. The Linca sheep represents one of the most important – but least known – biocultural legacies of the Mapuche people in Patagonia. These sheep, which arrived in the region along with the conquistadors more than three centuries ago, have been almost completely displaced by the Merino sheep breed. In this work we analyse the principal components that characterise the producers of Linca sheep. These components are the key for the conservation of this traditional practice and takes a substantial part of local zoological knowledge (LZK). Interviews with artisans (n = 51) who know, require or use Linca wool, either know the breeders, enabled us to contact and interview 13 families who preserve these sheep. Based on an interpretative study we identified 3 biocultural components and 11 analytical variables. Through this analysis of the archetypes, within this universe of producers, we recognized three profiles: Veteran, Tenacious, and Emotionally Attached. The families who have preserved this ancient practice were assigned to one of the three groups based on the shortest Euclidean distance and information obtained from the interviews. Among the main characteristics of these producers the important role played by women stands out, as they preserve and transmit knowledge of the textile language and maintain the diversity of the Linca sheep, transforming their family units into guardians of the biocultural inheritance of this local breed.